Tissue plasminogen activator (tPA) treatment for COVID_19 associated acute respiratory distress syndrome (ARDS): A case report (Bangladesh Critical Care Journal, 2021)
Coagulopathy has proven to be a common complication of the novel coronavirus SARS-CoV-21. Some of the COVID-19 associated pneumonia patients exhibit relatively preserved lung compliance and high alveolar‐arterial oxygen gradient. Pathology reports consistently demonstrate diffuse pulmonary microthrombi on autopsy, consistent with a vascular occlusive etiology of respiratory failure rather than the more classic findings of ARDS2. Pulmonary microthrombi induced respiratory failure is very difficult to prove because the patients are so critically ill that transfer to CT suit to do CTPA often becomes unsafe for the patients. Moreover, performing V/Q scan is increasingly difficult in such settings. Here we report a case of severe COVID-19 associated respiratory failure who was treated with tissue plasminogen activator (tPA) on clinical ground.Bangladesh Crit Care J March 2021; 9(1): 49-51